The Effect of Working Capital and Long-Term Debt on Net Profit at PT Medco Energi Internasional Tbk (Case Study Listed on the Indonesian Stock Exchange for the 2015-2022 Period) - Julianti, Marshela; Rijanto , Raden (Formosa Journal of Sustainable Research, 2024)
This research aims to determine the effect of working capital and long-term debt on net profit. This research conducted quantitative research using an associative descriptive approach. The 2015-2022 financial report is a secondary data source used for this research. The sample was taken using a non-probability sampling technique using a purposive sampling method with certain criteria, namely the quarterly financial report of PT Medco Energi Internasional Tbk for 2015-2022. To test the influence analysis, Pearson product moment analysis, deterministic coefficient analysis and hypothesis testing with the t test and F test were used. Based on the analysis, it turns out that the correlation between working capital and net profit is 0.311, which is in the low category, and the correlation between long-term debt and net profit is 0.310, including in the low category. Based on the determination analysis, it shows that the largest contribution from the influence of long-term debt and working capital variables on net profit is 22.8%, and other variables not examined by researchers is 77.2%